2017
DOI: 10.1186/s13063-017-2172-4
|View full text |Cite
|
Sign up to set email alerts
|

TAILOR – tapered discontinuation versus maintenance therapy of antipsychotic medication in patients with newly diagnosed schizophrenia or persistent delusional disorder in remission of psychotic symptoms: study protocol for a randomized clinical trial

Abstract: BackgroundThe aim of the TAILOR trial is to investigate the effect of closely monitored tapering/discontinuation versus maintenance therapy with antipsychotic medication in patients with newly diagnosed schizophrenia or persistent delusional disorder and with minimum 3 months’ remission of psychotic symptoms.Methods and designTwo hundred and fifty patients will be included from the psychiatric early intervention program, OPUS, in two regions in Denmark. Inclusion criteria are: ICD-10 diagnoses schizophrenia (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
0
21
1
Order By: Relevance
“…The duration of these studies was limited, with three studies having follow-up for 1 year and the longest study lasting only 3 years. In contrast to Zipursky's findings, it has been estimated in a longitudinal cohort study that up to 40% of those who achieve remission after FEP may ultimately remain well without medication (Sturup et al, 2017).…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…The duration of these studies was limited, with three studies having follow-up for 1 year and the longest study lasting only 3 years. In contrast to Zipursky's findings, it has been estimated in a longitudinal cohort study that up to 40% of those who achieve remission after FEP may ultimately remain well without medication (Sturup et al, 2017).…”
contrasting
confidence: 63%
“…The longitudinal design of the study will enable measurement of associations between antipsychotic medication and brain changes. A Danish RCT plans to compare maintenance treatment with closely monitored tapering/discontinuation of antipsychotic medication over 1 year, in people with newly diagnosed schizophrenia or persistent delusional disorder who have had 3 months remission of psychotic symptoms (Sturup et al, 2017). While these RCTs should be informative, in the meantime, we are faced with decisions about the optimal dose and duration of antipsychotic medication for people recovering from FEP.…”
Section: Medication Discontinuation In First Episode Psychosis: Thinkmentioning
confidence: 99%
“…A benchmark of ten studies is often suggested for the conduct of a meta-regression, 38 however, numerous reviews have been conducted with fewer studies. 46 The problems associated with using a smaller number of studies are particularly related to multivariate meta-regression, 48 which we did not conduct in this study. There is a striking deficiency in the evidence base given how important the question of medication discontinuation after remission is to clinicians and patients.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, similar trials are being conducted: the TAILOR trial [49] (Denmark), the RADAR study (research into antipsychotic discontinuation and reduction; UK), the reduce trial [50] (Australia), and "A Guided Dose Reduction Trial for Patients with Remitted Psychosis" [51] (Taiwan).…”
Section: Discussionmentioning
confidence: 99%